Memory strategies focused on english vocabulary learning: A case study in a public high school in Loja City: Estrategias de memoria enfocadas en el aprendizaje de vocabulario en inglés: Un estudio de caso en Colegio Público de la ciudad de Loja - Agila Salazar, Javier Mauricio; Agila Salazar, Eliana Alexandra (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
The research " Memory Strategies Focused on English Vocabulary Learning: A Case Study in a Public High School in Loja City" aimed to determine the effectiveness of memory strategies focused on English vocabulary learning among students of a public high school in Loja City. This study examined how various memory strategies promote vocabulary acquisition and retention, as well as opportunities for students’ practice in real contexts. It also investigated the adaptability of memory strategies to individual student needs and their efficacy for learners with diverse language proficiency levels or specific learning requirements. This study involved implementing four memory strategies, such as creating mental linkages, applying images and sound, reviewing well, and employing action, within the classroom setting over 12 weeks. Data collection methods included pre and post-assessments, student surveys, and classroom observations. Preliminary findings suggest that the use of specific memory strategies positively influences vocabulary retention and fosters a deeper understanding of language concepts. Finally, this research showed that memory strategies motivated vocabulary learning improvement and provided insights into improving language learning experiences for high school students.